2020
DOI: 10.3390/molecules25245811
|View full text |Cite
|
Sign up to set email alerts
|

New Insights for Red Propolis of Alagoas—Chemical Constituents, Topical Membrane Formulations and Their Physicochemical and Biological Properties

Abstract: The main objectives of this study were to evaluate the chemical constitution and allergenic potential of red propolis extract (RPE). They were evaluated, using high performance liquid chromatography (HPLC) and the release of β-hexosaminidase, respectively. A plethora of biologically active polyphenols and the absence of allergic responses were evinced. RPE inhibited the release of β-hexosaminidase, suggesting that the extract does not stimulate allergic responses. Additionally, the physicochemical properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…In a comparative study carried out by Bi et al [ 39 ] using PLA and PLA/PVA/SA electrospun fiber membranes for wound healing in vitro and in vivo, the authors observed that isolated PLA fibers allowed for the acceleration of wound healing in rats. The developed membrane system will be able to act synergistically between the hydrophilic membrane (promoting exudate absorption) [ 32 ], PLA (protein deposition) [ 39 ], and RPE (antioxidant, anti-inflammatory, and healing activity) [ 4 ]. The analyses described in this work reveal that the developed membrane has characteristics suitable for its use in in vitro and in vivo biological assays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a comparative study carried out by Bi et al [ 39 ] using PLA and PLA/PVA/SA electrospun fiber membranes for wound healing in vitro and in vivo, the authors observed that isolated PLA fibers allowed for the acceleration of wound healing in rats. The developed membrane system will be able to act synergistically between the hydrophilic membrane (promoting exudate absorption) [ 32 ], PLA (protein deposition) [ 39 ], and RPE (antioxidant, anti-inflammatory, and healing activity) [ 4 ]. The analyses described in this work reveal that the developed membrane has characteristics suitable for its use in in vitro and in vivo biological assays.…”
Section: Discussionmentioning
confidence: 99%
“…Its main feature is its high liquid absorption capacity. This characteristic is important for the manufacture of biomaterials to accelerate the wound healing process [ 3 , 4 ]. Biodegradable and bioabsorbable synthetic polymeric materials have been extensively investigated, and they are promising in the development of biomedical devices for application at the heart of tissue recovery [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such molecules are usually polyphenols and their derivatives, but also other compounds, from both natural and synthetic sources, have been employed with remarkable results. Ceria [79], curcumin [80], hydroxycinnamic acid derivatives, such as p-coumaric and ferulic acids [81], tannic acid [82], propolis [83], natural plant extracts [84][85][86], anthocyanins [87] and many other phytochemicals within nanocomposites have been tested for their ROS scavenging activities with relevant effects, especially in the case of diabetic chronic wounds, where over-production of ROS can impair angiogenesis and results in continuous inflammation [88][89][90].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%